2011
DOI: 10.1002/jrs.2738
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying amino acid and protein substitution using Raman spectroscopy

Abstract: Raman spectroscopy can be a powerful tool for the characterization of modified amino acids and proteins. In addition to the potential for quantitative results, it offers the advantage of not requiring any sample preparation. Modification of amines and thiols on amino acids and proteins are common reactions used for medical, biological, food, and agricultural purposes. We hypothesized that the Raman spectrum could be used to quantify the reactions and would be more informative than typical characterization tech… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 56 publications
1
19
0
Order By: Relevance
“…Numerous issues such as price uncertainty, manufacturing costs, environmental disposal, and geo‐political concerns are affecting the petroleum‐based polymer industry. As an alternative, since 1980s there is an increasing interest in the development of biodegradable nonpetroleum‐based polymers 1–4. However, the price of these nonpetroleum‐based polymers [e.g., poly(lactic acid), PLA] is high and not competitive with petroleum‐based polymers (e.g., polyethylene terephthalate, PET) 4.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous issues such as price uncertainty, manufacturing costs, environmental disposal, and geo‐political concerns are affecting the petroleum‐based polymer industry. As an alternative, since 1980s there is an increasing interest in the development of biodegradable nonpetroleum‐based polymers 1–4. However, the price of these nonpetroleum‐based polymers [e.g., poly(lactic acid), PLA] is high and not competitive with petroleum‐based polymers (e.g., polyethylene terephthalate, PET) 4.…”
Section: Introductionmentioning
confidence: 99%
“…As an alternative, since 1980s there is an increasing interest in the development of biodegradable nonpetroleum‐based polymers 1–4. However, the price of these nonpetroleum‐based polymers [e.g., poly(lactic acid), PLA] is high and not competitive with petroleum‐based polymers (e.g., polyethylene terephthalate, PET) 4. Therefore, the development of lower cost nonpetroleum‐based polymers is needed.…”
Section: Introductionmentioning
confidence: 99%
“…22 It was found that lysine preferably substitutes at the α-carbon at pH 9, which would be expected from the pK a of the α-and ε-amine. Using FT-IR spectroscopy, substitution reactions can be followed in solution through the change in the amine on the amino acid (Fig.…”
Section: Resultsmentioning
confidence: 98%
“…This experimental result can be explained by theory of SRS enhancement by fluorescence. The fluorescent seeds can linearly amplify intensity of the spontaneous Raman noise of SRS, shown as Eqn (2) in which the intensity of Stokes line I s (ν s , L) is also decided by gain length L besides Raman noise I sn (ν s ), fluorescent seeds I seed (ν s ), gain coefficient g s , intensity of pumping light I p , and attenuation coefficient α. Moreover, comparing with the effect of I seed (ν s ), the gain length L in e-index decides distinctly on the intensity of Stokes line.…”
Section: Influence Of Fluorescence Seeding Positionmentioning
confidence: 99%
“…Therefore, in recent years, there are extensive applications in nonlinear optics, biological, and other fields. [1][2][3] However, the SRS spectrum of molecules is always a multistage cascade spectrum dominated by active mode with maximum Raman cross section. [4] The depletion of the pumping laser intensity by this SRS buildup prevents the significant amplification of SRS of other Raman active modes.…”
Section: Introductionmentioning
confidence: 99%